Thalidomide surveillance and pharmacovigilance in Brazil - an overview - Lisiane Freitas Leal; Daniel Marques Mota (Fundação Oswaldo Cruz (FIOCRUZ), 2020)
Introduction: The thalidomide is probably the best-known teratogenic drug and still results in cases of severe physical deformities in children born in Brazil. The purpose of this work is to present the overall context of  surveillance and pharmacovigilance of thalidomide in Brazil. Method: This article presents a narrative review of current literature concerning thalidomide regulation, policies, and pharmacovigilance in Brazil. Results: New cases of congenital abnormalities whose phenotype is compatible with thalidomide embryopathy were identified  in the last ten years, while the approval of thalidomide for new indications was recently updated. The mechanisms of diagnosing thalidomide embryopathy are complex, remaining the challenge in distinguishing this condition from other congenital abnormalities. The increasing number of thalidomide users in Brazil is correlated with the occurrence of embryopathy and the real extension of the rationality of its use is largely unknown. Additionally, our pharmacovigilance and surveillance systems are predominantly based on voluntary reports,  issues that remains over the years. Conclusions: The policies have improved over the years  to prevent the fetus from being exposed to thalidomide, and current regulation establishes rules for controlling its distribution, prescription, dispensation, and use. Brazilian surveillance  system is manual and pharmacovigilance is supported by voluntary reports. The failure of the system to properly control the thalidomide use and its effects might lead to serious consequences to the community; therefore, this subject deserves constant attention.